2014
DOI: 10.1186/1472-6882-14-192
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative activity and induction of apoptotic by ethanolic extract of Alpinia galanga rhizhome in human breast carcinoma cell line

Abstract: BackgroundWe investigated the potential of galangal rhizomes to induce cytotoxic and apoptotic effects in the cultured human breast carcinoma cell line, (MCF-7) in compare with the non-malignant (MRC-5) cells.MethodsBoth cells were cultured in DMEM medium and treated with galangal rhizomes for three consecutive days. The percentage of apoptotic cells was determined by flow cytometry using Annexin-V fluorescein isothiocyanate.ResultsThe results showed that the ethanolic extract of galangal rhizomes decreased ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 70 publications
2
33
0
1
Order By: Relevance
“…[21][22][23] Thus, a growing investigation on the chemical constituents and bioactivities of this genus has been carried out since 1955. 24 Consequently, Alpinia species were proved to have various biological activities including antiulcer, 25 antiemetic, [26][27][28] antibacterial, [29][30][31] antitumor, [32][33][34] hypoglycemic, 35 cardioprotection, 36 antifungi, 37 neuroprotection, 38,39 and antianxiety activities. 40 Up to 2015, this genus contributed about 252 papers.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Thus, a growing investigation on the chemical constituents and bioactivities of this genus has been carried out since 1955. 24 Consequently, Alpinia species were proved to have various biological activities including antiulcer, 25 antiemetic, [26][27][28] antibacterial, [29][30][31] antitumor, [32][33][34] hypoglycemic, 35 cardioprotection, 36 antifungi, 37 neuroprotection, 38,39 and antianxiety activities. 40 Up to 2015, this genus contributed about 252 papers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, IC 50 of ARCE in COR-L23 cells, a lung cancer cell line, was 5.4-13.3 μg/ mL and IC 50 of ARCE in MCF7 cells, a breast cancer cell line, was 5.4-170 μg/mL. (26,27) ARCE was also reported to induce apoptosis in PC-3 cells, a prostate cancer cell line, in concentration of 100 μg/mL, 69% of total tested PC-3 cells were induced into apoptosis. (28) This suggested that ARCE has higher cytotoxic activity in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that Alpinia galanga induced apoptosis in MCF-7 cells, as determined by flow cytometry. 47 The active compound, 1'S'-1'-acetoxychavicol acetate were found to provide inhibition of the growth of oral squamous cell carcinoma in in vitro or in vivo by inhibition of the constitutive activation of NF-κB through suppression of IKKα/β activation Figure 3. The effect of the compound is also correlated with a down-regulation of NF-κB regulated gene (FasL and Bim), including proinflammatory (NF-κB and COX-2) and proliferative (cyclin D1) biomarkers in tumor tissue Table 1. 48 Alpinia galanga was found to cause antitumor activity.…”
Section: Anti-diabetic Activitymentioning
confidence: 99%